Capital structure of exporter SMEs during the financial crisis : evidence from Portugal - Lisboa, Inês (2017)
This study aims to identify the most important determinants to explain the capital structure of exporter SMEs during the financial crisis. Capital structure is measured using three alternative ratios: total debt, long-term debt, and short-term debt, as the impact of the determinants can depend on debt maturity. Analysing an unbalanced sample of 277 Portuguese exporter SMEs, from 2008 until 2014, and using a panel data methodology, estimating the models with fixed effects for firms, the results suggest that size, profitability, asset structure, non-debt tax shields, growth, liquidity, and age are important determinants for explaining firms’ capital structure. Furthermore, exports intensity and crisis effect do not impact a firm’s indebtedness. Findings are consistent with the hierarchy of funds proposed by the Pecking Order Theory. The Trade-off Theory is also important, as fixed asset can be used as collateral in the case of a firm’s bankruptcy. Additionally, results suggest that exporter SMEs hold more short-term than long-term debt, especially small-sized firms. Finally, companies’ debt ratio presents a constant tendency during the period analysed.